ATTRACTING FOREIGN DIRECT INVESTMENTS: THE CASE OF LATGALE REGION - Ežmale, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Recent theoretical and empirical studies show that foreign direct investment (FDI) is crucial for sustainable development of countries and regions. The various discussions among the regional development institutions in Latvia on the importance of improving the environment for successful attraction of foreign investments have been initiated, as well as new strategic initiatives are in the process of development. The aim of the paper is to analyse the latest trends of inward FDI flows in Latvia and Latgale region in the context of global FDI trends. To attain the aim, the global FDI trends, the inward FDI flows in Latvia and Latgale region, as well strategic framework of Latgale region for attracting FDI were analysed.